PENGARUH EARNING PER SHARE (EPS), PRICE EARNING RATIO (PER), DEBT TO EQUITY (DER), RETURN ON ASSET (ROA), DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM Studi Kasus pada Perusahaan Go Public Sektor Property dan Real Estate yang Terdaftar di Bursa Efek In - Putri Hermawanti; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2016)
This research had purpose to analyzed some of the fundamental factors of financial ratios that could be used as a signal for investors to predicted stock prices on companies in a sector that is growth in Indonesia, which was Property and Real Estate sectors. Variables that examined in this study were the Earning Per Share (EPS), Price Earning Ratio (PER), Debt to Equity Ratio (DER), Return on Assets (ROA) and Return on Equity (ROE) on the stock price, either partially or simultaneously on the Property and Real Estate sectors companies that have been listed in the Indonesia Stock Exchange in 2010 - 2014 . This research was an explanatory research with a total sample of 34 companies x 5 years = 170 observation data from a total population of 494 companies from all sectors listed on the Indonesia Stock Exchange, and then conducted a purposive sampling technique in order to got the number of samples. The analysis technique used was multiple regression analysis and hypothesis testing using t test partial, F test simultaneously with the level of significance of 5% and a determination coefficient test. The analysis showed the data have fulfilled classical assumption, including normally distributed data , no symptoms of multikolinearitas, there were no symptoms of autocorrellation and heteroscedasticity. The regression results Earning Per Share (EPS), Return on Assets (ROA) and Return on Equity (ROE) were partially significant effect on stock prices. While Price Earning Ratio (PER) and Debt to Equity Ratio (DER) partially were not significant effect on stock prices. These five variables used in this study (EPS, PER, DER, ROA and ROE) simultaneously affect the stock price of 47.2 %. The variables that had the strongest influence was Earning Per Share (EPS). While the remaining 52.8 % influenced by other factors that were not examined in the research. As a sector that was developing fast, the Company is expected to managed its financial performance well so it could bring out huge profits to expand the business even more widely to the outside of Indonesia without had use a high amount of liabilities.